Correlation of Stress Level, Nutrient Intake, and Emotional Eating Behavior with Nutritional Status among High School Students - Hidayat, Annisa Tantyana; Sinaga, Tiurma; Nurdiani, Reisi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The aim of the study was to determine the correlation between stress level, nutrient intake and eating behavior with nutritional status among 92 high school students aged 16 to 18 years from the Public High School (SMAN) 1 Kalianda. The Educational Stress Scale for Adolescents (ESSA), Dutch Eating Behavior Questionnaire (DEBQ), and anthropometric measurements were used for data collection. The results showed that the most likely factor to trigger stress was related to the study workload. About 44.6% of the subjects were found to be an emotional eaters. There was significant correlation of stress level, energy, protein, and carbohydrate intake with nutritional status (p<0.05). Based on the result, stress was an important factor that can influence the nutritional status